HUMAN RIGHTS CATEGORIZED JUS COGENS AND IT’S RELATION TO THE RIGHT OF EDUCATION - Fattah, Virgayani (Tadulako Law Review, 2017)
Jus cogens as a norm of general international law accepted and recognized by the international community as a whole with the main characteristics is the nature of non derogable rights.The right to education is a fundamental human right, so that its existence can’t be reduced under any circumstances based on the importance and importance of education for children.The national education policy is not yet fully aligned with the international human rights instruments causing the development of education sector not yet fully based on human rights.The Government is obliged to fulfill the right to education primarily in relation to the budget for building and repairing school buildings and improving the quality of education in Indonesia, as set out in the International Human Rights Instrument, in particular the Covenant on Ecosystem Rights.The importance of the right to education as the primary vehicle for lifting and empowering children from poverty, as a means to participate actively and totally in the development of its social community and as a powerful road to humanity.